2014
DOI: 10.1158/0008-5472.can-14-1220
|View full text |Cite
|
Sign up to set email alerts
|

NGF Blockade at Early Times during Bone Cancer Development Attenuates Bone Destruction and Increases Limb Use

Abstract: Studies in animals and humans show that blockade of nerve growth factor (NGF) attenuates both malignant and non-malignant skeletal pain. While reduction of pain is important, a largely unanswered question is what other benefits NGF blockade might confer in bone cancer patients. Using a mouse graft model of bone sarcoma, we demonstrate that early treatment with an NGF antibody reduced tumor-induced bone destruction, delayed time to bone fracture, and increased the use of the tumor-bearing limb. Consistent with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 43 publications
(56 reference statements)
2
51
0
Order By: Relevance
“…Cohorts consisted of both sham and MIA rats treated with either vehicle or muMab 911, experimenters blinded to all treatments. This dose of muMab 911 attenuated hyperalgesia in auto-immune arthritis 17 and bone cancer pain 18 . Pain behaviour was assessed twice weekly after model induction, studies were terminated on Day 28 (Supplementary fig.…”
Section: Methodsmentioning
confidence: 99%
“…Cohorts consisted of both sham and MIA rats treated with either vehicle or muMab 911, experimenters blinded to all treatments. This dose of muMab 911 attenuated hyperalgesia in auto-immune arthritis 17 and bone cancer pain 18 . Pain behaviour was assessed twice weekly after model induction, studies were terminated on Day 28 (Supplementary fig.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, a humanized monoclonal antibody (tanezumab) is already in clinical trials for its analgesic activity in chronic rheumatoid and back pain. Interestingly, in murine models, anti-NGF antibodies have been shown to decrease pain caused by bone metastases of prostate cancer and to attenuate bone destruction (20,21). Therefore targeting proNGF/NGF, and more generally neurotrophic factors, could also have an additional positive impact by reducing cancer-associated pain, but this perspective warrants further preclinical and clinical investigations.…”
Section: Potential Antineurogenic Therapies In Cancermentioning
confidence: 99%
“…Finally, to date, only sympathetic and parasympathetic nerves have been implicated in tumor progression and the role of sensory nerves has not yet been reported. Sensory nerves can eventually innervate primary tumors and metastases, thus contributing to tumor-associated pain as demonstrated in pancreatic (5) and prostate cancers (21).Therefore, a possible involvement of sensory fibers in tumor progression, although not demonstrated at this stage, cannot be excluded.…”
Section: Future Directionsmentioning
confidence: 99%
“…Blocking antibodies against NGF, and pharmacological inhibitors against TrkA, have been developed and some are already in clinical trials for their potent analgesic effect in rheumatoid and back pain (Longo and Massa, 2013). Interestingly, in the mouse it has been shown that anti-NGF antibodies can decrease the pain caused by bone metastasis and to attenuate bone destruction (Jimenez-Andrade et al ., 2011; McCaffrey et al ., 2014). Therefore targeting NGF/proNGF in cancer could also have an additional impact by reducing cancer pain.…”
Section: Neurotrophin-induced Neurogenesis In Tumor Tissuesmentioning
confidence: 99%